Asymmetric Synthesis of Axinellamines A and B. Issue 15 (8th March 2016) - Ma, Zhiqiang; Wang, Xiao; Ma, Yuyong; Chen, Chuo
Abstract: Axinellamines A and B are broad‐spectrum antibacterial pyrrole–imidazole alkaloids that have a complex polycyclic skeleton. A new asymmetric synthesis of these marine sponge metabolites is described herein, featuring an oxidative rearrangement and an anchimeric chlorination reaction. Abstract : From start to end : Axinellamines A and B are two dimeric pyrrole–imidazole alkaloids that have unusually high nitrogen and halogen atom contents. An asymmetric synthesis of these structurally complex natural antibiotics is described.